And Safety Protection Coordination Tasks Of Health For Heritage Habitat Limoges [Tender documents : T32589322] (MENA Report, 2016)
Main features: the market is subject to a single lot. benefits establish a market purchase orders, multi-attribute (2 Maximum beneficiaries subject to a sufficient number of applications and offers), whose benefits will likely vary as follows: No minimum annual maximum amount: EUR 90.000,00 () HT market duration is fixed at 1 year, renewable 1 time for 1 year in the conditions of ccap